REVIEWING THE TRACES OF ISLAMIC CIVILIZATION IN THE OLD BANTEN REGION - Irsyad Leihitu (Indonesian Journal of Islamic History and Culture, 2023)
The Old Banten region is proof of the greatness of the Banten Sultanate, which once stood in the west of Java Island for nearly three centuries. Many experts have studied the historical data, such as the explorer's travel notes or ancient maps, and done a lot of excavation to discover evidence that describes the splendor of the Banten Sultanate civilization. Even so, several archaeological data around the area are still untouched and can be explored. Based on the studies conducted, by combining the latest research, historical sources, and field observation data, the results show a match between the historical data and the current archaeological evidence. This paper also explores the areas considered as potential for future research.